Proposal Intensity Adequacy of Expiratory Effort and Heart Rate Behavior During the Valsalva Maneuver in Preadolescents - Paschoal,Mario Augusto (2014)
Background: When performing the Valsalva maneuver (VM), adults and preadolescents produce the same expiratory resistance values. Objective: To analyze heart rate (HR) in preadolescents performing VM, and propose a new method for selecting expiratory resistance. Method: The maximal expiratory pressure (MEP) was measured in 45 sedentary children aged 9-12 years who subsequently performed VM for 20 s using an expiratory pressure of 60%, 70%, or 80% of MEP. HR was measured before, during, and after VM. These procedures were repeated 30 days later, and the data collected in the sessions (E1, E2) were analyzed and compared in periods before, during (0-10 and 10-20 s), and after VM using nonparametric tests. Results: All 45 participants adequately performed VM in E1 and E2 at 60% of MEP. However, only 38 (84.4%) and 25 (55.5%) of the participants performed the maneuver at 70% and 80% of MEP, respectively. The HR delta measured during 0-10 s and 10-20 s significantly increased as the expiratory effort increased, indicating an effective cardiac autonomic response during VM. However, our findings suggest the VM should not be performed at these intensities. Conclusion: HR increased with all effort intensities tested during VM. However, 60% of MEP was the only level of expiratory resistance that all participants could use to perform VM. Therefore, 60% of MEP may be the optimal expiratory resistance that should be used in clinical practice.